Taking punishment into your own hands: an experiment on the motivation underlying punishment - Dürsch, Peter; Müller, Julia (Discussion paper series, 2010)
In a punishment experiment, we separate the demand for punishment in general from a possible demand to conduct punishment personally. Subjects experience an unfair split of their earnings from a real effort task and have to decide on the punishment of the person who determines the distribution. First, it is established whether the allocator's payoff is reduced and, afterwards, subjects take part in a second price auction for the right to (physically) carry out the act of payoff reduction. This auction only resolves who will punish, not whether punishment takes place, so only subjects with a demand for personal punishment should bid.
Online publiziert: 2010
Keywords: Arbeitspapier; Graue Literatur